High-resolution seafloor sedimentological mapping: the case study of Bagnoli-Coroglio site, Gulf of Pozzuoli (Napoli), Italy. Issue 6 (2nd July 2020) - Innangi, Sara; Tonielli, Renato; Di Martino, Gabriella; Guarino, Antimo; Molisso, Flavia; Sacchi, Marco
ABSTRACT: We present a new seafloor sedimentological map of Bagnoli-Coroglio SIN (Sites of National Interest) in the Gulf of Pozzuoli (Napoli), Italy, based on the analysis of the acoustic backscatter, calibrated with grain size distribution of sampled surficial marine deposits. Geophysical and ground-truthing (geological) data were acquired during a series of marine surveys designed for a seafloor characterisation aimed at remediation of the marine environment offshore the dismissed industrial area of Bagnoli. This study describes the acquisition and processing of the multibeam echo-sounder (Reson SeaBat 7125 high-resolution) backscatter data recorded during geophysical survey and illustrates the approach followed in the construction of a high-resolution seafloor map of the Bagnoli-Coroglio offshore.